Pengaruh Kepemimpinan Dan Manajemen Kepala Sekolah Terhadap Motivasi Kerja Guru Di Sekolah Dasar Kecamatan Batukliang Utara Kabupaten Lombok Tengah - Busairi, Busairi (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The purpose of this study was to analyze the influence of the principal's leadership and management on the work motivation of teachers in elementary schools in North Batukliang District, Central Lombok Regency. The research method is a survey with a quantitative approach. The population in the study were all teachers and school principals in North Batukliang District, Central Lombok Regency, which amounted to 138 people who were civil servants. The instrument used is a questionnaire that has been tested for validity and reliability. The results showed that the leadership and management of school principals had a positive influence on teacher work motivation and became a determining factor in the level of teacher work motivation. The leadership and managerial ability of the principal is important to continue to be developed and improved because the higher the competence possessed, the more positive the teacher's work in teaching will be